2021
DOI: 10.2138/am-2020-7508
|View full text |Cite
|
Sign up to set email alerts
|

Fluid source and metal precipitation mechanism of sediment-hosted Chang'an orogenic gold deposit, SW China: Constraints from sulfide texture, trace element, S, Pb, and He-Ar isotopes and calcite C-O isotopes

Abstract: The source of fluids and mechanism of metal precipitation in sediment-hosted, disseminated orogenic gold deposits are ambiguous. Pyrite texture, trace element, S, Pb and HeAr isotope compositions of sulfides and CO isotope data of calcite from Chang'an orogenic gold deposit in the Ailaoshan orogenic belt, SW China, were studied to provide a new genetic model for the sediment-hosted orogenic gold deposit, and furthering knowledge of the source of fluids and their mechanism of metal precipitation. Orebodies at C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(5 citation statements)
references
References 115 publications
0
5
0
Order By: Relevance
“…The lamprophyre dikes have narrow ranges of 206 Pb/ 204 Pb (18.50–18.59), 207 Pb/ 204 Pb (15.60–15.65) and 208 Pb/ 204 Pb (38.75–38.84), which overlap with those of gold-related sulfides in the Ailaoshan gold belt ( Supplementary Data ) [ 91 , 92 ]. The gold-rich rims of ore pyrites uniformly display a limited range of δ 34 S values around 0‰ [ 6 , 93 , 94 ], similar to those expected for a mantle source for the lamprophyre dikes that are spatially related to the gold deposits.…”
Section: Discussionmentioning
confidence: 85%
“…The lamprophyre dikes have narrow ranges of 206 Pb/ 204 Pb (18.50–18.59), 207 Pb/ 204 Pb (15.60–15.65) and 208 Pb/ 204 Pb (38.75–38.84), which overlap with those of gold-related sulfides in the Ailaoshan gold belt ( Supplementary Data ) [ 91 , 92 ]. The gold-rich rims of ore pyrites uniformly display a limited range of δ 34 S values around 0‰ [ 6 , 93 , 94 ], similar to those expected for a mantle source for the lamprophyre dikes that are spatially related to the gold deposits.…”
Section: Discussionmentioning
confidence: 85%
“…Gold mineralization is a process associated with structural deformation, fluid flow, fluid-rock reaction, and related changes in physico-chemical conditions of oreforming fluids (e.g., Sibson et al, 1988;Cox, 1995;Sibson, 1996;Sausse et al, 2001;Williams-Jones et al, 2009;Weatherley and Henley, 2013;Peterson and Mavrogenes, 2014;Yang et al, 2021Yang et al, , 2022. Many studies have demonstrated that structure-fluid feedback produces and/or destroys permeability by mineral dissolution and/or precipitation with mass and volume changes (Fig.…”
Section: Structure-fluid Feedback Triggering Gold Depositionmentioning
confidence: 99%
“…1). The host rocks for these Au deposits are Triassic sandstone and slate for Xiaoshuijing, Carboniferous to Triassic ophiolitic mé lange for Zhenyuan and Jinchang, Permian dolostone for Tongchang, and Neoproterozoic diorite for Daping, Ordovician turbudite for Chang'an (Li et al, 2019(Li et al, , 2023Wang et al, 2020;Yang et al, 2021bYang et al, , 2023. More geological characteristics for each deposit can be found in Table 1.…”
Section: Geological Settingmentioning
confidence: 99%